POS0111 BENEFICIAL EFFECT OF TEMPORARY METHOTREXATE WITHDRAWAL ON B AND T CELL RESPONSES UPON SARS-CoV-2 VACCINATION IN PATIENTS WITH RHEUMATOID ARTHRITIS OR PSORIATIC ARTHRITIS - Castañeda, S.; Vicente-Rabaneda, E.; Martínez-Fleta, P.; Triguero-Martinez, A.; Uriarte-Ecenarro, M.; Gutiérrez-Rodríguez, F.; Quiroga Colina, P.; Romero, A.; García Castañeda, N.; García-Vadillo, J. A.; Valero, C.; Llorente, I.; et al. (Annals of the rheumatic diseases, 2024)
Background:At the beginning of the COVID-19 pandemic there were controversial opinions regarding the possibility of temporary interrupting immunomodulatory treatments in rheumatic patients to enhance the immune response to the COVID-19 vaccine. Previous published works have raised the concern that methotrexate (MTX) might have a negative effect on immune response upon COVID-19 vaccine administration in this population. In this context, we postulated that temporary MTX interruption after COVID-19 vaccine administration could be beneficial for rheumatoid arthritis (RA) and psoriatic arthritis (PsA) patients in terms of improving both humoral and cellular responses, based on prior data on influenza vaccine.Objectives:Primary Objective: To evaluate the impact on B and T cell responses to COVID-19 vaccine of 1 or 2 weeks of MTX withdrawal following each vaccine dose in patients with RA or PsA. Secondary Objective: To analyze the adverse events in terms of flares of the disease.Methods:Single-centre, randomized, prospective study. Adult RA and PsA patients treated with MTX at stable dose were recruited between March and September 2021 (first vaccination campaign) and randomly assigned to 3 groups: MTX-maintenance, and MTX-withdrawal for 1 wk or 2 wks after each COVID-19 vaccine dose. Samples were collected before and 30 days after complete vaccination. Multi-antigen cytometric bead array assays to detect specific antibodies to several SARS-CoV-2 antigens and ELISPOT assays measuring interferon (IFN)-y and interleukin (IL)-21 were performed. Multivariable analyses with Stata v.14 were used to control the effect of possible confounding variables. The rates of disease relapses were recorded.Results:216 Patients were included (178 RA, 38 PsA), of whom 72 maintained MTX unchanged, and 71 and 73 withdrew MTX for 1 wk and 2 wks, respectively. Population characteristics are shown in Table 1. COVID-19 occurred in 47 patients before complete vaccination. Participants were vaccinated with BNT162b2 (71%), ChadOX-1-S (14%), mRNA-1273 (6%) and Ad26.COV2.S (9%). There were no significant differences in comorbidities (HT, DL, DM, COPD, asthma, CV disease, cancer), types of vaccines or previous COVID-19 infection across groups. On average COVID-19 vaccination elicited good levels of humoral and cellular responses, which were higher in patients previously infected with SARS-CoV-2. Humoral response was higher with mRNA vaccines. MTX withdrawal was associated with a significantly higher number of good responders for anti-S antibodies and significantly higher titres of anti-S IgA and IgM antibodies, anti-RBD IgG antibodies and neutralising antibodies in patients without previous COVID-19, especially in the 2-wks withdrawal group (Figure 1). Regarding cellular response, MTX withdrawal, especially the 2 wks group, was associated with higher IFN-γ secretion both in patients without and with previous COVID-19, but no differences were found for IL-21 across groups. Regarding safety, the rate of relapse was low, either using the DAS criteria (15%) or the physician’s criteria (12%), and the majority were mild or moderate. To highlight, there were no significant differences in the number of RA/PsA relapses across groups. Higher baseline CRP was the only factor associated with relapse: OR 1.77, 95%CI [1.03-3.03], p=0.037.Conclusion:Our data suggest that a brief MTX interruption following COVID-19 vaccination doses in patients with RA or PsA improves humoral and cellular immune responses, without significant increase of relapses, especially in patients without previous COVID-19 infection and with good disease control.REFERENCES:NIL.Acknowledgements:All members of the Rheumatology and Immunology Departments of Hospital Universitario de La Princesa.Disclosure of Interests:Santos Castañeda: Ministerio de Economía y Competitividad (Instituto de Salud Carlos III) (grant no. PI21/0147 to SC, PID-2020-120412RB-I00 and PDC2021-121797-I00 to FS-M) and co-funded by European regional development fund (ERDF) “A way to make Europe”, and also by REACT-EU-INMUNOVACTER-CM and P2022/BMD7209-INTEGRAMUNE from Comunidad Autónoma de Madrid., Esther Vicente-Rabaneda: None declared, Pedro Martínez-Fleta: None declared, Ana Triguero-Martinez: None declared, Miren Uriarte-Ecenarro: None declared, Francisco Gutiérrez-Rodríguez: None declared, Patricia Quiroga Colina: None declared, Ana Romero: None declared, Noelia García Castañeda: None declared, Jesús A. García-Vadillo: None declared, Cristina Valero: None declared, Irene Llorente: None declared, Ana Ortiz: None declared, Eva Tomero Muriel: None declared, Maria Aranzazu Alfranca: None declared, Rosario Garcia-Vicuña: None declared, Francisco Sánchez-Madrid: None declared, Isidoro González-Álvaro: None declared.